RM-CSTV: An effective high-resolution method of non-line-of-sight millimeter-wave radar 3-D imaging - Liu Xinyuan; Wei Shunjun; Pu Wei; Cai Xiang; Wen Yanbo; Guo Shisheng; Kong Lingjiang (National Science Open)
Non-line-of-sight (NLOS) imaging is a novel radar sensing technology that enables the reconstruction of hidden targets. However, it may suffer from synthetic aperture length reduction caused by ambient occlusion. In this study, a complex total variation (CTV) regularization-based sparse reconstruction method for NLOS three-dimensional (3-D) imaging by millimeter-wave (mmW) radar, named RM-CSTV method, is proposed to improve imaging quality and speed. In this scheme, the NLOS imaging model is first introduced, and associated geometric constraints for NLOS objects are established. Second, an effective high-resolution NLOS imaging method based on the range migration (RM) kernel and complex sparse joint total variation constraint, dubbed as modified RM-CSTV, is proposed for 3-D high-resolution imaging with edge information. The experiments with multi-type NLOS targets show that the proposed RM-CSTV method can provide effective and high-resolution NLOS targets 3-D imaging.